Unilateral dorsiflexor strengthening with mirror therapy to improve motor function after stroke: A pilot randomized study. (2nd July 2019) - Simpson, Daniel; Ehrensberger, Monika; Horgan, Frances; Blake, Catherine; Roberts, David; Broderick, Patrick; Monaghan, Kenneth
Abstract: Background: Independently, cross‐education, the performance improvement of the untrained limb following unilateral training, and mirror therapy have shown to improve lower limb functioning poststroke. Mirror therapy has shown to augment the cross‐education effect in healthy populations. However, this concept has not yet been explored in a clinical setting. Objectives: This study set out to investigate the feasibility and potential efficacy of applying cross‐education combined with mirror therapy compared with cross‐education alone for lower limb recovery poststroke. Methods: Thirty‐one chronic stroke participants (age 61.7 ± 13.3) completed either a unilateral strength training (ST; n = 15) or unilateral strength training with mirror‐therapy (MST; n = 16) intervention. Both groups isometrically strength trained the less‐affected ankle dorsiflexors three times per week for 4 weeks. Only the MST group observed the mirror reflection of the training limb. Patient eligibility, compliance, treatment reliability, and outcome measures were assessed for feasibility. Maximal voluntary contraction (MVC; peak torque, rate of torque development, and average torque), 10‐m walk test, timed up and go (TUG), Modified Ashworth Scale (MAS), and the London Handicap Scale (LHS) were assessed at pretraining and posttraining. Results: Treatment and assessments were well tolerated without adverse effects. No between group differences were identified for improvement in MVC, MAS, TUG, or LHS. Only the combined treatment was associated with functional improvements with the MST group showing an increase in walking velocity. Conclusion: Cross‐education plus mirror therapy may have potential for improving motor function after stroke. This study demonstrates the feasibility of the combination treatment and the need for future studies with larger sample sizes to investigate the effectiveness of the treatment.